2021
DOI: 10.13005/msri/180306
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Properties of Coffea Arabica/Reduced Graphene Oxide Nanocomposite prepared by green synthesis

Abstract: The present study focuses on an efficient eco-friendly method for reducing graphene oxide (rGO) using Coffea arabica leaf extract for bio-medical applications for the first time to the best of our knowledge. The reduction of graphene oxide (GO) using Coffea arabica leaves was verified through Raman, X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM). The XRD peaks corresponding to GO at 2 =10º have dissapeared on reduction of GO to rGO and the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The biologically active compounds in coffee leaves are excellent reductants, capping agents, and stabilizers that can be used to green synthesis of NPs. Coffee leaf extract (CLE) has been used to synthesize reduced graphene oxide nanocomposite which possessed antioxidant and anti-inflammatory activities ( Perera et al, 2021 ). To our best knowledge, there is no research using coffee leaves to synthesize ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The biologically active compounds in coffee leaves are excellent reductants, capping agents, and stabilizers that can be used to green synthesis of NPs. Coffee leaf extract (CLE) has been used to synthesize reduced graphene oxide nanocomposite which possessed antioxidant and anti-inflammatory activities ( Perera et al, 2021 ). To our best knowledge, there is no research using coffee leaves to synthesize ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly our study also proves that both GO and rGO showed relatively better scavenging effects of free radicals. Since the basal hydroxyl group disturbs the radical stabilization, GO provides less strong free radical scavenging property compared with positive control 51 . From the experimental data, the IC 50 value for reference standard ascorbic acid was 38.7272 μg/ml, for GO 48.77 μg/ml, and rGO 92.30 μg/ml.…”
Section: Resultsmentioning
confidence: 98%
“… 117–120 Targeted delivery systems for anti-inflammatory drugs have also been investigated, such as loading the anti-inflammatory drug ibuprofen into a graphene oxide-chitosan system. 121 In summary, GFNs have been shown to play an important role in DDS and are favored by many researchers for their ability to rapidly deliver drugs and precisely target specific areas ( Table 1 ).…”
Section: Biomedicine Application Of Gfnsmentioning
confidence: 99%